Vállalkozóképző - tévés sorozat
The series consists of background material for the 21 part television series of P. Schiffer, including studies for by Péter Csanádi, László Fényes, Sándor Klein, Tibor Kuczi, Ágnes Vajda, and the film production diary. Interviews with entrepreneurs, and a study by Péter Szirmai form part of the series, too. Accruals not expected